Pengembangan Media Game Edukasi berbasis Macromedia flash Mata Pelajaran Matematika Materi Pecahan Di Kelas IV SD NU Sleman - Wibowo, Edy Wahyu; Abdillah, Abdillah; Nugroho, Wahyu (Universitas Muhammadiyah Magelang, 2020)
This study aims to develop a macromedia flash-based Educational Game Media suitable for use in fraction mathematics lessons. The research method used is a type of Research and Development (R & D). The model used is a modification of the model from Borg and Gall with the following stages: (1) research and information gathering, (2) planning, (3) initial product development, (4) limited trials, (5) initial product revision, (6) Main field trials, (7) operational product revisions, (8) operational field trials, (9) final product revisions, (10) Dissemination and implementation. The results showed that the educational Game Media based on macromedia flash was valid, so it was suitable for use in the mathematics learning process. Educational Game Media based on macromedia flash is also considered effective for improving learning outcomes based on the T Independent Sig test results. (p) 0.00 with conditions P <0.05 so that H0 is rejected. Paired T test results Sig. (p) 0.000 with conditions P <0.05 so that H0 is rejected also shows that the macromedia flash-based Educational Game Media has a significant impact on improving learning outcomes.